Relationships Between Upper-Plate Structure, Mantle Wedge Melting, and Fore-Arc Sliver Transport in the Nicaraguan Subduction Zone - Emily Carrero Mustelier; Karen M. Fischer; Junlin Hua; Isabella Gama; Peter C. La Femina; Machel Higgins (The Seismic Record)
This study images the base of the upper-plate lithosphere in the Nicaraguan subduction zone using common conversion point stacking of Sp phases and explores the relationships between deep upper-plate structure, subduction zone melting processes, and the arc-parallel transport of the Central American fore-arc sliver. We observe the negative velocity gradient associated with the upper-plate lithosphere–asthenosphere boundary in the Nicaraguan back-arc at depths of 60–80 km. However, the amplitude of the lithosphere–asthenosphere velocity gradient diminishes beneath the arc, consistent with a reduction in the shear-wave velocity of the deep upper-plate lithosphere. This zone lies above mantle wedge velocity anomalies which indicate upward-migrating partial melt, suggesting that ascending melt has altered and weakened the lithospheric mantle of the upper plate. In northwestern Nicaragua, the boundary of the Central American fore-arc sliver and the Caribbean plate, which is marked by a northeast decrease in geodetically measured arc-parallel surface velocities, lies above the northeast increase in the amplitude and localization of the lithosphere–asthenosphere velocity gradient. This correlation indicates that the kinematic margin of the Central American fore-arc sliver corresponds to a structural boundary that extends throughout the upper plate, and that is influenced by melt ascending from the mantle wedge.